2021
DOI: 10.51122/neudentj.2021.26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Medcem MTA, Medcem Pure Portland Cement and NeoMTA to Pediatric Restorative Materials to Shear Bond Strength

Abstract: Bu çalışmanın amacı, vital pulpa tedavilerinde kullanılan Medcem Saf Portland siman, Medcem MTA ve NeoM-TA'nın farklı pediatrik restoratif materyallere makaslama bağ dayanımını karşılaştırmaktır. Gereç ve Yöntemler: Makaslama bağ dayanım testi için standart akrilik bloklar (4*2 mm) hazırlandı. Üretici firmaların talimatları doğrultusunda hazırlanan kalsiyum silikat içerikli biyomateryaller (Medcem MTA, Medcem Saf Portland siman, NeoMTA) akrilik bloklardaki boşluklara yerleştirildi ve sertleşmeleri için önerile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…NeoMTA could be considered comparable to NuSmile-Neoputty in the main compositional constituents. Thus, when comparing the results of the present study to the study conducted by Duman et al (51) , it could be emphasized that using MDP containing adhesives in case of dealing with Equia Forte Fil would show no benefit for its bonding potential to NuSmile-Neoputty. The results of Duman et al, in 2021 (51) was found in agreement with the results of the present study; since both subgroups IIA (7.07±1.06 MPa) and IIB (7.07±1.45 MPa) revealed a statistically comparable shear bond strength values of no significant difference between them.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…NeoMTA could be considered comparable to NuSmile-Neoputty in the main compositional constituents. Thus, when comparing the results of the present study to the study conducted by Duman et al (51) , it could be emphasized that using MDP containing adhesives in case of dealing with Equia Forte Fil would show no benefit for its bonding potential to NuSmile-Neoputty. The results of Duman et al, in 2021 (51) was found in agreement with the results of the present study; since both subgroups IIA (7.07±1.06 MPa) and IIB (7.07±1.45 MPa) revealed a statistically comparable shear bond strength values of no significant difference between them.…”
Section: Discussionsupporting
confidence: 43%
“…Thus, when comparing the results of the present study to the study conducted by Duman et al (51) , it could be emphasized that using MDP containing adhesives in case of dealing with Equia Forte Fil would show no benefit for its bonding potential to NuSmile-Neoputty. The results of Duman et al, in 2021 (51) was found in agreement with the results of the present study; since both subgroups IIA (7.07±1.06 MPa) and IIB (7.07±1.45 MPa) revealed a statistically comparable shear bond strength values of no significant difference between them. Additionally, on focusing on the composition of Equia Forte Fil, the lack of calcium which is substituted by strontium could be a cause of weak bonding to NuSmile-Neoputty, even in case of direct application without an intervening adhesive layer, clarifying that presence of MDP containing adhesive or its absence would not affect the adhesive junction strength in case of bonding to Equia Forte Fil.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…However, in this study, the mean SBS of the adhesive-free MMTA and EFHF group (21.48 ± 8.95 MPa) showed a significant increase compared to the values reported by Duman et al (5.76 ± 3.63 MPa). Similarly, the mean SBS of the adhesive-free MMTA and FIILC group (9.79 ± 2.83 MPa) also exhibited higher values than those reported in the study conducted by Duman et al (6.06 ± 5.75 MPa) [ 6 ]. The observed difference in the mean SBS between the glass ionomer cement and MMTA groups in this study may be attributed to various factors, including variations in research conditions, sample size, and differences among practitioners.…”
Section: Discussionmentioning
confidence: 56%
“…Conclusions drawn from these investigations indicate that while Proroot MTA exhibits significantly enhanced clinical performance, it may trail behind more contemporary materials in certain aspects [ 4 , 5 ]. There is currently only one study on the SBS of Medcem MTA and Medcem Pure Portland Cement, which are prepared to meet all MTA indicators accepted in the market and are claimed by the manufacturer to exhibit extraordinary mechanical properties [ 6 ]. Hence, it is of utmost importance to compare them with well-established material in clinical practice for an extended duration, such as Proroot MTA.…”
Section: Introductionmentioning
confidence: 99%